Pengembangan Sistem Informasi Manajemen Masjid Al Ghifari berbasis Web - Muhammad Rezky Sayuthi Putra; Nurudin Santoso; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Al Ghifari Mosque is one of the mosques in Lowokwaru District, Malang City. Al Ghifari Mosque management consists of activity management and financial management. Activity Management consists of managing information on routine activities, prayer schedules, and incidental activities. Financial management consists of recording the mosque's financial income and expenditure. The problem with the misuse of Al Ghifari Mosque's activity management is the publication of activity information on social media, namely Instagram and Facebook. Lack of information delivery using Instagram and Facebook not all information about activities can be conveyed and only people with these social media get the information. One of the problems in the financial management of the Al Ghifari Mosque is the recording of financial income and expenditure which is recorded using a book. The disadvantage of recording financial statements using manual books is that they are lost or damaged. To solve the existing problems, a web-based mosque management information system was developed. The development of this system uses the waterfall model and uses an object-oriented approach, and is built using the CodeIgniter framework. The system has been tested using unit testing, integration, and validation. Unit and integration testing uses white-box testing techniques, and tests are validated using black-box testing techniques with each test being 100% valid. This system can be run on various browsers, such as Google Chrome, Firefox, and Opera. The result of this research is a web-based mosque management information system.